Phenotypic evaluation of the resistance in f1 carnation populations to vascular wilt caused by fusarium oxysporum f.sp. dianthi (2012)
One of the most important phytosanitary problems of the carnation crops in Colombia and in the entire world is vascular wilting produced by Fusarium oxysporum f.sp. dianthi. Currently, an effective treatment against the pathogen does not exist; the search for resistant varieties has been the most successful method for control of this disease. Breeding programs are vital to solving the problem of the carnation fusariosis. The objective of this research was the phenotypic evaluation of carnation F1 populations, products of contrasting crossing, resistant per susceptible to F. oxysporum f.sp. dianthi, in order to determine if the resistance is inherited in the lines. This information will contribute to the selection of material and to the successful introduction of the resistant characteristic, whose expression is commercially acceptable, to the gene pool. The methodology adopted was a phenotypic evaluation of the response to the parasite in the population (450 individuals) and in the parental. This evaluation estimated the area under the curve (AUDPC), using a scale of symptoms reported for carnation vascular wilt. Three different phenotypes were established with this evaluation. The moderately susceptible one is the predominant phenotype and an analysis of phenotypic frequencies was carried out on it. The results show that the individuals of the evaluated F1 population were distributed between two extreme ranges, resistant and susceptible; this shows that there is segregation for the trait resistant to F. oxysporum f.sp dianthi. We did not observe clearly differentiated classes, i.e. with complete absence or presence of the disease, indicating a possible control of the resistance in the evaluated carnation material, governed by more than one gene and with a possible additive genetic action.